An escherichia coli expression system for the extracellular secretion of cyclodextrin glucanotransferase - Mohd. Anuar, author; Rosli Mohd. Illias, author; Penang International Postgraduate Convention (2nd: 2008: Pulau Pinang) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL